Pembentukan Karakter Religius Pada Anak Usia Dini di Raudhatul Athfal Safinatunnajah Kebumen - Inwarul Marzuki; Benny Kurniawan; Nginayatul Hasanah (Tarbi: Jurnal Ilmiah Mahasiswa, 2023)
The objectives of this study are to: (1) analyze the formation of religious character and (2) analyze methods in the formation of religious character in early childhood in Raudhatul Athfal Safinatunnajah Petanahan Kebumen. This research is a type of field research, where the authors collect data by conducting in-depth studies in the form of interviews with principals, teachers and parents as key informants (key informants in schools) as well as observations on phenomena that occur and document these data. Then, the data is analyzed using qualitative descriptive methods intended to describe situations of a factual nature. The collected data is analyzed using data reduction, presentation, and verification. The results of this study concluded that the formation of religious character in early childhood in Raudhatul Athfal Safinatunnajah Petanahan Kebumen was good which was adapted to the school's vision and integrated through school programs such as greetings, getting used to praying before activities, habituation to read Asmaul Khusna and short letters, habituation of congregational Dhuha prayers, commemoration of Islamic Holidays, activities in the month of Ramadan, infaq or shodaqoh, and manasik Hajj. In shaping religious character in early childhood in Raudhatul Athfal Safinatunnajah Petanahan Kebumen uses various methods such as demonstration methods, practices, examples, advice, habituation, exemplary, reward and punishment whose function is so that these religious programs can run effectively.